The effectiveness of pulsed electromagnetic field therapy in patients with shoulder impingement syndrome: A systematic review and meta-analysis of randomized controlled trials. - Hsun-Yi Wang; Yi-Jen Chen; I-Ching Huang; Chao-Ruei Lin; Ko-Long Lin; Chia-Hsin Chen (PLoS ONE)
We performed a systematic review and meta-analysis to assess the efficacy of pulsed electromagnetic field (PEMF) therapy in treating patients with shoulder impingement syndrome. We sourced data from PubMed, the Cochrane Library, and Embase databases up until June 19, 2024. Our analysis included randomized controlled trials (RCTs) that evaluated the impact of PEMF therapy on pain levels and functional capacity in these patients. In total, four RCTs involving 252 participants were included. The pooled data indicated that PEMF therapy significantly reduced short-term pain (standardized mean difference [SMD] = -0.34, 95% confidence interval [CI] = -0.66 to -0.01, three RCTs, n = 166) and improved both short-term (SMD = 0.4, 95% CI = 0.08 to 0.73, three RCTs, n = 166) and long-term functional capacity (SMD = 0.6, 95% CI = 0.33 to 0.88, three RCTs, n = 212). The aforementioned results all achieved clinical significance. The observed low heterogeneity for short-term pain, along with short term and long-term functional capacity, highlights the sustained robustness and consistency of the effect on functional capacity over time. These results suggest that PEMF therapy is statistically effective in enhancing short-term pain relief and improving both short-term and long-term functional capacity in patients with shoulder impingement syndrome, with clinically significant benefits. However, the study limitations include a small sample size and variability in PEMF protocols, highlighting the necessity for standardized methodologies in future research.